Estimation of interface tension in the structured disperse systems using rheological data - G. A. Grigoriev; R. G. Allahverdov; U. U. Stoliarov (Тонкие химические технологии, 2006)
On the base of full flow curves of structured oil-in-water emulsions with 0,12 to 0,32 part by volume of oil phase the main oil particle diameters and yield strength were determined. A novel equation was obtained with the use of Deriagin equation and equation for estimation of the yield strength of structured emulsion. This equation permits us to estimate the surface tension in the water medium-oil particle interface (P-M) with the aid of experimental data. The P-M value in such systems was shown to be equal 0,3 mN/m and found to be almost constant in the investigated region of concentrations. For the comparison an estimation of the same value with the use of the Gamaker constant is also given in the present paper.